Rekonstruksi Kontekstual Poligami Era Kontemporer: (Studi Tematik QS. An-Nisa ayat 3) - Septi Megasari; Komarudin Sassi (Prodi Ilmu Al-Qur'an dan Tafsir, 2025)
Polygamy constitutes one of the most critical issues in the discourse of Islamic family law and continues to generate debate, particularly with regard to the principles of justice and the protection of women. Qur’an Surah An-Nisa (4):3 is often understood textually as providing absolute legitimacy for the practice of polygamy. Such an understanding, however, frequently neglects the historical and social context as well as the moral message of the Qur’an, which emphasizes justice and rahmah (compassion). In contemporary realities, the practice of polygamy not infrequently results in injustice and increased vulnerability for women and children. This study employs a qualitative method using thematic (maudhu‘i) and contextual approaches to Qur’anic interpretation. The analysis focuses on Surah An-Nisa (4):3 by situating it within the framework of maqāṣid al-sharī‘ah, particularly the protection of life, human dignity, and social justice. The findings indicate that polygamy in the Qur’an is not a normative command but rather a conditional social solution that emerged from a context aimed at protecting vulnerable groups, such as orphans and women. The requirement of justice constitutes a fundamental prerequisite, which the Qur’an itself acknowledges as difficult to realize perfectly. Therefore, the practice of polygamy devoid of justice and rahmah stands in contradiction to the core values of Islam. This study underscores the importance of a critical and humanistic reinterpretation to ensure that Qur’anic teachings remain relevant and just within contemporary society.